Determinan Indeks Pembangunan Manusia Di Wilayah Pesisir Aceh Bagian Barat - Adrisa Auldri; Syarifah Azzahra; Rangga Permana Putra; Asnidar Asnidar; Ahmad Ridha (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Aceh Province has 23 districts/cities with a Human Development Index level similar to the national Human Development Index. Several districts/cities in Aceh Province have a Human Development Index below the national Human Development Index. This research aims to analyze the Human Development Index and the factors that influence it in the western part of the Aceh coastal region for 2010-2022. This research is quantitative. The variables used in this research are the Human Development Index, Economic Growth, Poverty Level, and Gini Index. The panel data method is used for analysis through cross-data from 7 districts/cities in the western Aceh coastal region and time series data for 2010-2022. The results of this research show that Economic Growth has a negative and significant effect on the Human Development Index, Poverty Level has a positive and insignificant effect on the Human Development Index, and the Gini Index has a positive and significant effect on the Human Development Index in the western Aceh coastal region for the 2010-2022 period.